SAT-352 Comprehensive Genetic Analysis of Cortisol-Producing Adenomas - Hoxie, Jessie (J Endocr Soc, 2019)
Background: Cortisol-producing adenomas (CPA) are the most common cause of adrenal Cushing’s syndrome. Next-generation sequencing (NGS) has recently facilitated the identification of somatic mutations that cause autonomous cortisol production by these tumors. The most commonly mutated gene in CPAs is PRKACA, resulting in hyper-activation of the protein kinase A (PKA) signaling pathway. Somatic mutations of GNAS, PRKAR1A, and CTNNB1 have also been identified in CPAs. However, direct mutation analysis of CPAs using formalin-fixed paraffin-embedded (FFPE) materials and immunohistochemistry (IHC)-guided targeted NGS has not been done before. Objective: To investigate the prevalence of somatic mutations in CPAs using FFPE tissue sections and targeted NGS. Methods: FFPE adrenal tumor tissue from 37 patients with Cushing’s syndrome who underwent adrenalectomy in our institution was used. IHC of HSD3B2 and CYP17A1 was performed. Aldosterone synthase (CYP11B2) IHC was also performed on tumors with low CYP17A1 expression and one from a patient with concomitant primary aldosteronism with Cushing’s syndrome. IHC-guided gDNA isolation was performed from 40 functional tumor samples [38 CPAs and two CPA-adjacent aldosterone-producing adenomas (APAs)]. Targeted NGS was implemented to identify somatic mutations involved in the tumors. The panel of targeted NGS included PKA pathway related genes (PRKACA, PRKAR1A, GNAS) and β-catenin (CTNNB1), as well as aldosterone-driver genes (KCNJ5, CACNA1D, ATP1A1, ATP2B3). Results: Somatic mutations were found in 63% (24/38) of CPAs. The two most commonly mutated genes were PRKACA (29%, n= 11/38) and CTNNB1 (24%, n= 9/38). GNAS mutations were found in 8% (3/38) of the CPAs and a PRKAR1A mutation was found in one CPA (3%). Of the two CPA-adjacent APAs, one had a KCNJ5 mutation, while the other had a CACNA1D mutation. Clinically, the autonomous cortisol production resulting from these CPAs was dichotomized into either overt or subclinical Cushing’s syndrome. Intriguingly, the majority of PRKACA mutations were found in the overt Cushing’s syndrome group (62%, n= 8/13) compared to only 1/23 (4%) of the subclinical Cushing’s syndrome cohort. The overt Cushing’s syndrome group also contained the single PRKAR1A mutation (8%, n=1/13). Furthermore, CTNNB1 (39%, n= 9/23) and GNAS (13%, n= 3/23) mutations were exclusively observed in subclinical Cushing’s syndrome patients. Conclusion: Targeted NGS on FFPE CPA tissue identified somatic mutations in 63% of tumors. CPAs causing overt Cushing’s syndrome appear to have a distinct mutation profile compared to the tumors observed in subclinical Cushing’s syndrome.